Peningkatan Mutu Pengelolaan TPA Assakinah - Novi Puji Lestari; Haryo Prasodjo; Hafid Adim Pradana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2019)
Daycare purpose of providing services to children aged 0 - 6 years who are forced to leave their parents because of work or other obstacles, in addition to providing services related to the fulfillment of children's rights to grow and develop, get protection and affection, and the right to participate in their social environment. TPA is a service that organizes education and care for children from birth to the age of six (with the priority of children under the age of 4 years). The Community Service program is focused on improving the quality and management of As Sakinah Dau's daycare in order to create a child-friendly and attractive form of child care like most daycare centers. The Child Care Center has been established for a long time but in terms of school profile and other information related to supporting schools is quite less..